STOP: Can We Minimize OR Traffic?. (27th September 2015) - Elliott, Sara; Parker, Stacy; Mills, Judi; Meeusen, Lindsay; Frana, Theresa; Anderson, Marie; Storsveen, Amy; White, Amy
Abstract: Perioperative nurses at our institution voiced concerns about the amount of traffic in the ORs. We formed a workgroup consisting of perioperative nurses, educators, and leaders and initiated a quality improvement (QI) project to identify the amount of OR traffic that occurs during a procedure. The workgroup developed a check sheet to record door swings, staff classifications, reasons for opening the door, and the number of people in the OR at 15‐minute intervals. Baseline results showed that average door swings ranged from 33 per hour in general surgery to 54 per hour in cardiac surgery. Nurses accounted for the most traffic, citing retrieving supplies as the main reason. Interventions focused on decreasing nurse traffic for retrieval of supplies in general surgery. Follow‐up observations showed that average door swings increased to 41 per hour in general surgery, but nurse traffic decreased. Monitoring and limiting traffic could positively affect patient safety and outcomes.